Influence of Digital Marketing and E-WoM on Repurchase Intention through Brand Trust of Feel Matcha Surabaya - Mohammad Hendrew Priasmono; Muhammad Fachmi; Dhiyan Septa Wihara; Ika Diyah Candra Arifah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to analyze the influence of digital marketing and electronic word of mouth (E-WoM) on repurchase intention through brand trust among Feel Matcha consumers in Surabaya. Using a quantitative explanatory approach, data were collected from 101 active TikTok users who had purchased Feel Matcha products and analyzed using SEM-PLS. The results indicate that digital marketing significantly influences repurchase intention (β = 0.256; p = 0.035) and brand trust (β = 0.375; p < 0.001). Likewise, E-WoM has a stronger significant effect on repurchase intention (β = 0.415; p = 0.001) and brand trust (β = 0.526; p < 0.001). However, brand trust does not significantly mediate the effect of digital marketing (β = 0.044; p = 0.394) or E-WoM (β = 0.062; p = 0.400) on repurchase intention. These findings indicate that consumer repurchase decisions are driven more by the attractiveness, authenticity, and credibility of TikTok content than by long-term trust formation. The study contributes to consumer behavior theory in digital platform contexts and offers practical insights for optimizing TikTok-based marketing strategies to strengthen customer loyalty.